2000
DOI: 10.1007/s002340050005
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebral blood flow in MELAS shown by Tc-99m HMPAO brain SPECT

Abstract: We report cerebral SPECT studies on two siblings with the syndrome of mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MELAS). Tc-99m HMPAO brain SPECT was performed 8, 19 and 30 days after a stroke-like episode in one case and 10 days after a stroke-like episode, 6 h after a partial seizure and as a follow-up study in the other. Increased blood flow was seen in both these patients with stroke-like episodes due to MELAS. The cause of the increased blood flow is uncertain, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In patients with an ND1 defect the dopamine transporter SPECT was normal 87 . In MELAS patients with a SLE, the cerebral blood flow has been found increased on Tc-99m HMPAO cerebral SPECT 88 . In acute SLLs hyperperfusion has been documented within the lesions 24 .…”
Section: Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 94%
“…In patients with an ND1 defect the dopamine transporter SPECT was normal 87 . In MELAS patients with a SLE, the cerebral blood flow has been found increased on Tc-99m HMPAO cerebral SPECT 88 . In acute SLLs hyperperfusion has been documented within the lesions 24 .…”
Section: Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 94%
“…Recently there have been a number of radiological studies to determine the mechanisms contributing to the onset of a stroke‐like episode and also to monitor its progression as they can migrate to other regions of the brain. There is evidence that during preclinical or acute onset of a stroke‐like episode, focal hyperperfusion can be detected by either arterial spin labelling or SPECT and can manifest before any structural abnormalities might be seen on MRI . In addition to this, there are reports of vasodilation following magnetic resonance angiogram and impaired cerebrovascular reactivity .…”
Section: Neurological Symptoms and Neuropathologymentioning
confidence: 99%
“…In addition perfusion‐studies with MRI showed hyperintensity, indicating hyperperfusion in the early stages of the SLL [36]. There are also studies with xenon‐CT, showing increased cerebral blood flow in the subacute or chronic stage from 1 week to 8 months after onset of a SLE [9,31], being attributed to a local increase in lactic acid [45]. Focal hyperperfusion in the acute stage and diffuse hypoperfusion in the chronic stage of a SLL were also found on HMPAO‐SPECT.…”
Section: Imaging Of Sllsmentioning
confidence: 99%